Reappraisal of sauropod dinosaur diversity in the Upper Cretaceous Winton Formation of Queensland, Australia, through 3D digitisation and description of new specimens - Beeston, S.L.; Poropat, Stephen; Mannion, P.D.; Pentland, Adele; Enchelmaier, M.J.; Sloan, T.; Elliott, D.A. (2024)
Skeletal remains of sauropod dinosaurs have been known from Australia for over 100 years. Unfortunately, the classification of the majority of these specimens to species level has historically been impeded by their incompleteness. This has begun to change in the last 15 years, primarily through the discovery and description of several partial skeletons from the Cenomanian-lower Turonian (lower Upper Cretaceous) Winton Formation in central Queensland, with four species erected to date: Australotitan cooperensis, Diamantinasaurus matildae, Savannasaurus elliottorum, and Wintonotitan wattsi. The first three of these appear to form a clade (Diamantinasauria) of early diverging titanosaurs (or close relatives of titanosaurs), whereas Wintonotitan wattsi is typically recovered as a distantly related non-titanosaurian somphospondylan. Through the use of 3D scanning, we digitised numerous specimens of Winton Formation sauropods, facilitating enhanced comparison between type and referred specimens, and heretofore undescribed specimens. We present new anatomical information on the holotype specimen of Diamantinasaurus matildae, and describe new remains pertaining to twelve sauropod individuals. Firsthand observations and digital analysis enabled previously proposed autapomorphic features of all four named Winton Formation sauropod species to be identified in the newly described specimens, with some specimens exhibiting putative autapomorphies of more than one species, prompting a reassessment of their taxonomic validity. Supported by a specimen-level phylogenetic analysis, we suggest that Australotitan cooperensis is probably a junior synonym of Diamantinasaurus matildae, but conservatively regard it herein as an indeterminate diamantinasaurian, meaning that the Winton Formation sauropod fauna now comprises three (rather than four) valid diamantinasaurian species: Diamantinasaurus matildae, Savannasaurus elliottorum, and Wintonotitan wattsi, with the latter robustly supported as a member of the clade for the first time. We refer some of the newly described specimens to these three species and provide revised diagnoses, with some previously proposed autapomorphies now regarded as diamantinasaurian synapomorphies. Our newly presented anatomical data and critical reappraisal of the Winton Formation sauropods facilitates a more comprehensive understanding of the mid-Cretaceous sauropod palaeobiota of central Queensland.